2018
DOI: 10.3329/jninb.v3i1.36268
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Morphological Differences of Ruptured Saccular Aneurysm in Different Sites of Anterior Circulation in Patients Presenting with Subarachnoid Haemorrhage

Abstract: Background: All sites of intracranial aneurysms have always been considered together in most of the studies of risk factors of aneurysm rupture. Therefore, it is not known whether some risk factors predispose to aneurysm rupture at a particular location. Morphologies also vary in accordance to different sites of the aneurysm. Objective: The purpose of the present study was to observe the differences in the risk factors, the size, aspect ratio and size ratio among the anterior circulation aneurysms. Methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(35 reference statements)
1
0
0
Order By: Relevance
“…About half of the population were within 51-60 years. This is consistent with Reaz Mahmud et al where the average age was 48.24±9.26 35 . Another two studies conducted in Bangladeshthe mean age was 45.00±9.4 and 45.9 years 36,37 .In an epidemiological study done in India had shown average age of subarachnoid hemorrhage in their population was 49.63 years 38 .Worldwide the mean age of aneurysmal rupture is in the range of 50 to 55 years.…”
Section: Discussionsupporting
confidence: 92%
“…About half of the population were within 51-60 years. This is consistent with Reaz Mahmud et al where the average age was 48.24±9.26 35 . Another two studies conducted in Bangladeshthe mean age was 45.00±9.4 and 45.9 years 36,37 .In an epidemiological study done in India had shown average age of subarachnoid hemorrhage in their population was 49.63 years 38 .Worldwide the mean age of aneurysmal rupture is in the range of 50 to 55 years.…”
Section: Discussionsupporting
confidence: 92%